2018
DOI: 10.1002/lary.27498
|View full text |Cite
|
Sign up to set email alerts
|

Sex bias in basic science and translational otolaryngology research

Abstract: Objectives/Hypothesis Recent studies revealed sex bias in surgical research. Although many diseases exhibit sex‐based clinically relevant differences, otolaryngology research has not been evaluated for sex reporting and sex‐based analysis. We postulate that a similar bias is prevalent in otolaryngology literature. Study Design Literature review. Methods Articles published from 2016 to 2017 in The Laryngoscope, Otolaryngology–Head and Neck Surgery, and JAMA Otolaryngology–Head and Neck Surgery were reviewed. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…As a result, the CFD findings can not be generalized to others due to inter-individual anatomic differences (13) . However, this highlights the previously demonstrated importance of providing subject sex and race data so that the applicability (external validity) of the findings can be assessed by the reader (28)(29)(30) . The findings presented here do agree with those of prior studies in different individuals (16)(17)(18)(19)(20) .…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 88%
“…As a result, the CFD findings can not be generalized to others due to inter-individual anatomic differences (13) . However, this highlights the previously demonstrated importance of providing subject sex and race data so that the applicability (external validity) of the findings can be assessed by the reader (28)(29)(30) . The findings presented here do agree with those of prior studies in different individuals (16)(17)(18)(19)(20) .…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 88%
“…Recent studies analyzing high‐impact general surgery and orthopedic surgery literature demonstrated that approximately one‐third of recently published studies performed analysis of outcomes by sex . A similar review of the otolaryngology literature by our institution found similar lack of sex‐ or gender‐based reporting of outcomes in three major otolaryngology journals . Males and females experience many conditions differently, including disease prevalence, symptom manifestations, and response to therapeutics.…”
Section: Discussionmentioning
confidence: 52%
“…Sex-based results reporting was only identified in 1% of the studies included [11]. Similar data exist in otolaryngology and orthopaedic research [12,13]. This study aimed to establish the prevalence of sex-specific reporting and the consideration of sex as a statistically controlled variable in preclinical and clinical research studies on renal cancer.…”
Section: Introductionmentioning
confidence: 79%